Bilateral Amygdala Radio-Frequency Ablation for Refractory Aggressive Behavior Alters Local Cortical Thickness to a Pattern Found in Non-refractory Patients - Gouveia, Flavia Venetucci; Germann, Jürgen; Devenyi, Gabriel A.; Fonoff, Erich T.; Morais, Rosa M. C. B.; Brentani, Helena; Chakravarty, M. Mallar; Martinez, Raquel C. R. (Frontiers in Human Neuroscience, 2021)
Aggressive behaviours comprise verbal and/or physical aggression directed towards self, others or objects and are highly prevalent among psychiatric patients, especially patients diagnosed with autism spectrum disorder and severe intellectual disabilities. Some of these patients are considered refractory to treatment and functional neurosurgery targeting the amygdala can result in widespread plastic brain changes that might reflect ceasing of some abnormal brain function, offering symptom alleviation. This study investigated cortical thickness changes in refractory aggressive behaviour patients that were treated with bilateral amygdala ablation and compared to control patients presenting non-refractory aggressive behaviour (3 refractory and 7 non-refractory patients, all males diagnosed with ASD and intellectual disabilities). The Overt Aggression Scale (OAS) was used to quantify behaviour and Magnetic Resonance Imaging was performed to investigate cortical thickness. Before surgery, both groups presented similar total OAS score, however refractory patients presented higher physical aggression against others. After surgery the refractory group showed 88% average reduction of aggressive behaviour. Imaging analysis showed that while refractory patients present an overall reduction in cortical thickness compared to non-refractory patients across both timepoints, the local pattern of thickness difference found in areas of the neurocircuitry of aggressive behaviour present before surgery is diminished and no longer detected after surgery. These results corroborate the hypotheses on induction of widespread neuronal plasticity following functional neurosurgical procedures resulting in modifications in brain morphology and improvement in behaviour. Further studies are necessary to determine the underlying cause of these morphological changes and to better understand and improve treatment options.